Burnout and Job Performance of Special Educators Working with Students Diagnosed with Autism Spectrum Disorder: A Case Study at Specialised Centre in Dubai - GURSHCHENKO, ANTONINA (2024)
This case study seeks to examine the effects of burnout on the key work performance indicators of special education teachers in a Dubai specialised centre for children diagnosed with Autism Spectrum Disorder (ASD) and the potential predictive relationship between various demographic characteristics like age, gender, education, years of experience, and the age group of the students they are working with, and three burnout dimensions: emotional exhaustion, depersonalisation, and personal accomplishment. This study employs a quantitative approach in its research design. The data revealed that there is no strong direct impact of burnout on the performance indicators of the special educators working with students diagnosed with ASD. Regarding the demographic variables that can potentially directly affect special educators' burnout, no confirmation was found that all three dimensions of burnout – emotional exhaustion, depersonalisation, and personal accomplishment – were equally affected by certain variables collectively. It was found that the age and experience of the special education teachers have an impact on emotional exhaustion. The education qualification may affect depersonalisation, and gender is associated with feelings of personal accomplishment of the special education teachers. Academics, educational leaders, special education centre managers, special education teachers, and policymakers can benefit from this research's results. When seeking to improve the educational experience for children with Autism Spectrum Disorder (ASD), it will be helpful to utilise the findings of this research to make informed decisions when addressing issues associated with the burnout of special education teachers working with children diagnosed with Autism. Keywords: burnout, special educators, performance